If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -36 = -33 Reorder the terms: -36 + 3x = -33 Solving -36 + 3x = -33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 3x = -33 + 36 Combine like terms: -36 + 36 = 0 0 + 3x = -33 + 36 3x = -33 + 36 Combine like terms: -33 + 36 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 7-4(x+8)+9=35 | | x^2+2x-10=20 | | x^2+y^2=2.25 | | 7.9y+8.4-2.04y= | | 3.09(j+4.6)= | | x+13=y | | 1E-15= | | 6(n-1)+2(n+1)=10+7n | | 4+3(x-7)+8=25 | | 1E-14= | | 25+x=325 | | 4(m+6)-3= | | 25x=325 | | 4r+s-2t=5 | | 8x+6=6x+36 | | 2x^3+5x^2+12x+30= | | -2x-2=32 | | 4(-1-7x)=332 | | -2(2x-9)=2 | | -7x+3=-74 | | 6(5x-9)=-264 | | 3(xb+5)= | | 1519.76=1.333333333*3.14*r^3 | | 3(2x+10)=78 | | 12j-(9j+7)= | | 2(-10-3x)=-32 | | 1519.76=1.333333333*3.14*r | | -7-3x=-25 | | -3-3x=-27 | | i=117*x-233500 | | -5+6x=-29 | | 6-3x=-12 |